Framework pengukuran kinerja rantai pasok industri kemasan plastik menggunakan metode SCOR-AHP - Deky Aryanto; Sawarni Hasibuan (Universitas Mercu Buana, 2021)
The manufacturing industry in general cannot be separated from the role of the plastic industry. In Indonesia, there are 925 companies that produce various kinds of plastic products for the food and beverage industry, automotive industry, pharmaceutical industry and other industries. Companies are faced with challenges to improve their supply chain competitiveness, while plastic packaging companies generally do not have a comprehensive performance measurement framework in their supply chains. The purpose of this research is to select and determine the level of importance of the Key Performance Indicator (KPI) for measuring the supply chain performance of the plastic packaging industry using the SCOR and AHP framework. In the initial stage, 45 KPIs were identified, from the results of expert validation, 29 KPIs were distributed to the dimensions of reliability, responsiveness, flexibility, cost, and assets. At the level 1 hierarchy the greatest level of importance is generated in the dimensions of reliability (A1), asset management (E1), responsiveness (B1), cost (D1), and flexibility (C1) with weights of 0.262, 0.209, respectively. 0.191, 0.175, and 0.163. The largest distribution of KPIs is on the reliability dimension, namely 32%, followed by the cost dimension of 16%, 12% responsiveness, flexibility and asset management have the same distribution, namely 4%. Based on the results of weighting using the AHP method, a supply chain performance measurement framework is recommended in the case of the plastic packaging industry.